Characterization of Balsamic Vinegars Using High-Performance Liquid Chromatography and Gas Chromatography - Kašpar, Michal; Česla, Petr (MDPI, 2022)
Vinegars are natural products manufactured by two-step fermentation. One of the most famous is balsamic vinegar, especially that produced in Modena, Italy. Its unique production process positively distinguishes it from other vinegars. There are basically three types of balsamic vinegar: common balsamic vinegar, Balsamic vinegar of Modena, and Traditional balsamic vinegar of Modena. The chemical analysis of these vinegars is mainly carried out by using gas or liquid chromatography, often coupled to mass spectrometric detection. Although gas chromatography is generally used for the determination of the overall profile of volatile organic compounds, furfurals, phenolic compounds, and organic acids, high-performance liquid chromatography is typically applied for the determination of amino acids, sugars, and polyphenols. The two complementary techniques, the combination of which is useful for the detailed characterization of balsamic vinegars, are reviewed and discussed in this article.
Charakterizace balsamikových octů pomocí vysokoúčinné kapalinové chromatografie a plynové chromatografie
Keywords: balsamic vinegar; gas chromatography; high-performance liquid chromatography; volatile compounds; phenolic compounds; balsamikový ocet; plynová chromatografie; kapalinová chromatografie; fenolické sloučeniny